Answer: 5x+y=21……equation 1 x-3y=9……equation 2 from1:y=21-5x…..equation 3 substitute y by 21-5x in equation 2 x-3(21-5x)=9 x-63+15x=9 x+15x=9+63 16x=72(we divide both sides by 16) 16÷16=72÷16 therefore x=9/2 or x=4,5 substitute x by 4,5 or 9/2 in equation 3 y=21-5(9/2) or y=21-5(4,5) y=-3/2 or y=-3/2 prove 5(9/2)-3/2=21 -3/2-3(9/2)=9 Log in to Reply

Answer:5x+y=21……equation 1

x-3y=9……equation 2

from1:y=21-5x…..equation 3

substitute y by 21-5x in equation 2

x-3(21-5x)=9

x-63+15x=9

x+15x=9+63

16x=72(we divide both sides by 16)

16÷16=72÷16

therefore x=9/2 or x=4,5

substitute x by 4,5 or 9/2 in equation 3

y=21-5(9/2) or y=21-5(4,5)

y=-3/2 or y=-3/2

prove

5(9/2)-3/2=21

-3/2-3(9/2)=9

Answer:x=9/2

y= -3/2

Step-by-step explanation:espero que te sirva:)